Analysis of Entrepreneurial Skills In Growing Competitive Advantages In "Fresh Milk" Micro, Small, And Medium Enterprises (MSMEs) In Gresik District: Analisis Skill Entreprenuer dalam Menumbuhkan Keunggulan Bersaing pada UMKM Fresh Milk di Kabupaten Gresik - Sutono Sutono (El-Qist: Journal of Islamic Economics and Business (JIEB), 2023)
One business actor who is quite resilient in facing intense competition is Micro, Small, and Medium Enterprises (MSMEs). The author designed this study to analyze and answer the influence of entrepreneurial skills in fostering competitive advantage in "Fresh Milk" MSMEs in Randu Padangan Village, Gresik. The method used by the author in this research is a quantitative approach. The number of samples in this research was 37 from "Fresh Milk" entrepreneurs in Randu Padangan Village using saturation sampling. The method for collecting data was a questionnaire and documentation. The data analysis techniques used in this research are the T-test and the R square-test. This study's results indicate a positive influence of entrepreneurial skills on competitive advantage in "Fresh Milk" MSMEs in Randu Padangan, Gresik. We can see these results from the results of research processed with the SPSS for Windows 17.0 program, which shows the results of the partial test Hs0 is rejected, and H1 is accepted if the results of t-count > t-table or sig-value < 0.05, which means that the entrepreneurial skill variable has a significant effect on the competitive advantage variable in "Fresh Milk" MSMEs in Randu Padangan Village. We can see the magnitude of the influence between variables from the coefficient of determination of 0.919, which means that 91.9% of the competitive advantage of "Fresh Milk" MSMEs in Randu Padangan Village is influenced by entrepreneurial skills. In comparison, the remaining 8.9% is influenced by other variables not included in this research.     Salah satu pelaku bisnis yang cukup tangguh dalam menghadapi ketatnya persaingan adalah para pelaku Usaha Mikro Kecil Menengah (UMKM). Penelitian ini diangkat untuk menganisis dan menjawab pengaruh skill enterpreneur dalam menumbuhkan keunggulan bersaing pada UMKM Fresh Mild di Desa Randupadangan Gresik. Adapun metode yang digunakan dalam penelitian ini menggunakan pendekatan kuantitatif. Jumlah Sampel penelitian ini sebanyak 37 pengusaha Fresh Milk di desa Randupadangan dengan menggunakan Sampling Jenuh, metode pengumpulan data menggunakan kuesioner (angket) dan dokumentasi. Teknik analisis data yang dipakai dalam penelitian adalah uji T dan Uji R Square. Hasil penelitian ini menunjukkan Adanya pengaruh skill entrepreneur terhadap keunggulan bersaing pada UMKM Fresh Mild Randu padangan di Gresik. Hasil tersebut dapat diketahui dari hasil penelitian yang diolah dengan program PASW Statistics 17 for windows menunjukkan hasil uji parsial H0 ditolak dan H1 diterima apabila hasil t hitung > t table atau nilai sig < 0,05 maka dapat diartikan bahwa variable skill entrepreneur memiliki berpengaruh secara parsial terhadap variabel keunggulan bersaing pada usaha mikro kecil menengah Fresh Milk di Desa Randu padangan. Besar pengaruh antar variabel dapat diliat dari hasil nilai koefisien determinasi sebesar 0,919 yang artinya 91,9% keunggulan bersaing usaha mikro kecil menengah Fresh Milk di Desa Randupadangan di pengaruhi oleh Skill Entrepreneur, sedangkan sisanya 8,9% dipengaruhi oleh variabel lain yang tidak dimasukkan dalam penelitian ini. Kata kunci: Skill Enterprenuer, UMKM.